Morphofunctional changes and mechanisms of their realization in developing lungs under influence of paracetamol and nimesulid - Kharchenko S.V.; Lazarev K.L. (Морфологія, 2012)
Actuality of organs and tissues normality development studying is conditioned on continuous growth of conge-nital abnormalies оn the base of greater drugs distribution. The anomalie s of lungs development unde r influence of paraceta-mol and nimesulide are examined and the possible mechanisms of their appearance are analysed. It is determined that lungs develop more slowly under action of paracetamol than in norm and paracetamol lead to development of bronchial asthma during postnatal period of life. Small in numbers researches of nimesulide influen ce demonstrate changes of lungs histogene-sis, which show up in thei r development deceleration.